Numerical Simulation of Bearing Capacity Relationship Between Tile Surface Annular Groove and Thrust Surface - Wentao Zhang; Yang Liu; Dongsheng Wang (Jixie chuandong)
In order to study the advantages of the annular groove of the tile surface on the bearing performance of the thrust sliding bearing，based on the theory of computational fluid dynamics (CFD)，the oil film analysis model of the inclined plane thrust sliding bearing with the annular groove is established. The law of influence of depth and width on the bearing performance of annular groove inclined plane thrust sliding bearing. The results show that the bearing capacity and peak oil film pressure of the thrust bearing increase first and then decrease with the increase in the proportion of the annular groove in the plane area，and as the proportion of the annular groove increases，the bearing temperature gradually decreases. When the width of the annular groove is constant，the increase of the depth makes the oil film pressure distribution of the thrust sliding bearing change obviously，and the bearing capacity shows a change law that first increases and then decreases，the depth of the annular groove remains unchanged，and the bearing capacity increases with the increase of the width of the annular groove Increase，adding a specific annular groove structure on the inclined plane thrust sliding bearing pad surface is beneficial to improve the bearing performance.